Influence of New Media on Public Opinion in the Formation of the Environmental Brand Image of the City (On the Example of Chelyabinsk, Russia) - Yana DOBRYNINA; Elena TROFIMENKO (Communications of International Proceedings, 2021)
The anthropogenic impacts on the environment that have increased in recent decades necessitate research focused on identifying and assessing changes in the environment. In this context, it is important and relevant to study the characteristics of a person's perception of the prevailing living conditions, sources of increased environmental hazards, and related concerns of the population. Authors defined that each person develops his own assessment of the condition of the environment, his or her own attitude towards it. Further, from the individual vision of the problem, a value-based social judgment is created, which is called public opinion. The object of public opinion in our study is Chelyabinsk and its environment, the subject of the study is the perception of the ecological situation resulting from the interaction of production activities (industries) with the natural conditions of the city. Moreover, within the framework of this work, the role of the Internet media in the formation of public opinion of city residents was studied.
Keywords: Public opinion; city image; new media; urban environment; ecological situation.